The Nordic Keyhole - Andersson, Cecilia (2021)
Front of pack nutrition label (FOPNL) could be used to guide consumers to healthier choices. FOPNL were therefore used as a tool for consumers to give guidelines in choosing healthy food. The FOPNL Nordic Keyhole has the criteria low amount of sugar, low amount of salt, low amount of fat, and high amount of dietary fiber and whole grain in food products. The overarching aim of the study was to investigate if and how food business operators use the Nordic Keyhole symbol as a guideline when producing healthy food. The used methods were a survey, discussion with food business operators and literature study. Identified challenges which the Swedish Food Agency has to work further with, were advertising. It is important for consumers that Nordic Keyhole products are appealing but remain healthy. It seems like the criteria salt, fat and whole grain have some issues depending on food category compared to the criterion sugar for which there were no issues mentioned. To be able to produce healthy products which consumer wants to buy, it is important for product developers to put focus on a packaging which looks healthy. Advantages and disadvantages were described for some FOPNL in Europe. Overall, all the respondents agree that they want to continue working with the Nordic Keyhole in Sweden. Finally, some positive aspects of the Nordic Keyhole were mentioned. More than half of the food producers label with the Nordic Keyhole. Food business operators generally have a positive attitude to the Nordic Keyhole.